Alterations in the expression level of visfatin in the lungs of piglets infected with PRRSV and its effect on PRRSV replication. (March 2022) - Zhang, Zhe-wei; Ansari, Abdur Rahman; Dong, Ling; Niu, Xiao-yu; Yang, Wen-jie; Li, Hui-zhen; Xu, Fen-liang; Yang, Ke-li; Song, Hui
Abstract: Porcine reproductive and respiratory syndrome (PRRS) is a highly contagious disease caused by PRRS virus (PRRSV), characterized by sow reproductive failure and respiratory symptoms in pigs of all ages. PRRSV mainly causes severe lung damage by invading alveolar macrophages. Visfatin is closely related to acute lung injury, immune response and inflammation along with virus invasion to the host. Therefore, the current study was performed to clarify the relationship between visfatin and PRRSV infection. We used ternary piglets to construct a piglet model to explore the expression of visfatin and tight junction protein in lung injury induced by PRRSV infection, and then further studied the inhibition effect of visfatin on PRRSV replication by PRRSV infection of Marc-145 cells. Our results indicated that both PRRSV attenuated and virulent infections could damage the lung tissues, which could not only lead to severe inflammatory reaction (such as increased expression of TNF-α, TGF-β, IL-8 and IL-10) in lung tissues of piglets, but also brought about the sharp decrease of ZO-1 and Tricellulin expressions resulting in impaired alveolar epithelial barrier. Meanwhile, we found significantly up-regulated expression of visfatin in lungs and serum of pigs after PRRSV infection that were related to both the degree of lung injury and the virulence of PRRSV strain. Moreover, visfatin might inhibit the PRRSV infection to Marc-145 cells in time dependent fashion. Hence, the current investigation provides the novel information about the effect of visfatin and PRRSV co-culture on Marc-145 cells and the effect of visfatin on PRRSV proliferation at different time points. Highlights: Clarification about the relationship between visfatin and PRRSV infection. Both PRRSV attenuated and virulent infections could damage the lung tissues. PRRSV infection leads to impairment of alveolar epithelial barrier. Significantly high visfatin expression in lungs and serum after PRRSV infection. Visfatin inhibits the PRRSV infection to Marc-145 cells in time dependent fashion.